Differential localization of carbachol- and bicuculline-sensitive pontine sites for eliciting REM sleep-like effects in anesthetized rats - FENIK, VICTOR B. (J Sleep Res, 2008)
Carbachol, a cholinergic agonist, and GABA(A) receptor antagonists injected into the pontine dorsomedial reticular formation can trigger rapid eye movement (REM) sleep-like state. Data suggest that GABAergic and cholinergic effects interact to produce this effect but the sites where this occurs have not been delineated. In urethane-anesthetized rats, in which carbachol effectively elicits REM sleep-like episodes (REMSLE), we tested the ability of 10 nL microinjections of carbachol (10 mM) and bicuculline (0.5 or 2 mM) to elicit REMSLE at 47 sites located within the dorsal pontine reticular formation at the levels −8.00 to −10.80 from bregma (B) (Paxinos and Watson, The Rat Brain in Stereotaxic Coordinates, Academic Press, San Diego, 1997). At rostral levels, most carbachol and some bicuculline injections elicited REMSLE with latencies that gradually decreased from 242 to 12 s for carbachol and from 908 to 38 s for bicuculline for more caudal injection sites. As the latencies decreased, the durations of bicuculline-elicited REMSLE increased from 104 s to over 38 min, and the effect was dose dependent, whereas the duration of carbachol-elicited REMSLE changed little (104– 354 s). Plots of REMSLE latency versus the antero-posterior coordinates revealed that both drugs were maximally effective near B-8.80. At levels caudal to B-8.80, carbachol was effective at few sites, whereas bicuculline-elicited REMSLE to at least B-9.30 level. Thus, the bicuculline-sensitive sites extended further caudally than those for carbachol and antagonism of GABA(A) receptors both triggered REMSLE and controlled their duration, whereas carbachol effects on REMSLE duration were small or limited by its concurrent REMSLE-opposing actions.